Role of transvaginal sonography in gynecological diagnosis at a tertiary care hospital - V., Sitalakshmi; Bansal, Alpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Transvaginal sonography (TVS) is very useful to assess the abnormalities in the anatomical structure of the uterus as well as endometrium. Not only this, it is capable of finding out any abnormalities of ovary, fallopian tubes, cervical structures as well as myometrium. The objective of the study was the role of transvaginal sonography in gynecological diagnosis at a tertiary care hospital. Methods: Present hospital based prospective study was carried out among 31 randomly selected eligible patients as per inclusion and exclusion criteria of the study for a period of one year at Department of Obstetrics and Gynecology of S. V. Medical College, Tirupati. All ethical guidelines were followed. A pre-designed and semi structured pre-tested questionnaire was prepared for entry of patient data. Results: Transvaginal sonography was more accurate in terms of evaluation of both tubes. Overall diagnostic accuracy of transvaginal sonography was 90.9%. It was found that the accuracy of clinical diagnosis was 100% in comparison to diagnosis by scan. In five cases, the clinical diagnosis of infertility was made as ovarian cyst and in all those cases it was confirmed. In three cases, the clinical diagnosis of infertility was made as fibroids and in all those cases it was confirmed. It was found that in cases of ectopic pregnancy, copper T missing loop and missed abortion, the clinical diagnosis was 100% accurate in comparison to scan diagnosis. Only in case of pelvic inflammatory disease, the accuracy of clinical diagnosis was 66% in comparison to scan diagnosis. Conclusions: Despite the few disadvantages of transvaginal sonography in measuring large pelvic masses, the smallest details of the masses yield valuable preoperative information. The more accurate delineation of internal echo characteristics scores the benefit over transvaginal sonography has its rightful place in gynecological practice has diagnostic and minimally invasive therapeutic tool.